BABUR - THE PRINCE OF GARDENS (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
In given article we will try to analyze history of architecture of Charbagh gardens and it`s evolution process. Moreover, we will try to clear up the role of Babur in formation of such kind of gardens. Lastly, we describe how Babur gardens has begun and its development over the years, also, we have given an evidence supporting our points.